Verbal communication disorders in brain damaged in post-strocke patinets in Benin.................... - KPADONOU GODONOU, TOUSSAINT; ALAGNIDE, HOUNTONDJI ETIENNE; NIAMA NATTA, DIDIER; HOUNGBEDJI, M. GERMAIN; ADJAKA, N. (My University, 2013)
........................
Keywords: strocke; Verbal communication; desorder; speech therapy; Bénin